Necrotising fasciitis of the thigh. (13th June 2013) - Haemers, K; Peters, R; Braak, S; Wesseling, F
Abstract : Necrotising fasciitis (NF) is an extremely virulent form of infectious fasciitis. It affects skin, subcutaneous fat and superficial and deep muscular fascia by rapidly progressive necrosis. Expeditious diagnosis and radical debridement is necessary to prevent the onset of sepsis, multisystem organ failure and possible death. Perforated rectal cancer resulting in NF can spread to the perineum and genitals known as Fournier gangrene. This case describes an unusual case of NF of the right thigh as first presentation highly suggestive for rectal cancer.